Rare pediatric synchronous bilateral testicular germ cell tumors of different pathological types: a case report - Feng, Yikun; Qu, Yu; Wu, Rongde; Liu, Wei; Du, Guoqiang (Frontiers in Pediatrics, 2024)
The occurrence of synchronous bilateral testicular germ cell tumors (BTGCTs) of different pathologic histologic types in pediatric patients is rare. We reported a case of a left testicular yolk sac tumor (YST) combined with a right testicular mature teratoma. Left orchiectomy and right testis-sparing surgery were performed. Retroperitoneal recurrence was noted 6 months after surgery. The patient underwent reoperation for the resection of a retroperitoneal mass, which was pathologically diagnosed as a recurrent YST. A full cycle of chemotherapy was then administered. No tumor metastasis or recurrence has yet been detected. We present this new case, and we review the previous literature on synchronous BTGCTs to explore the clinicopathologic features and summarize the diagnostic and therapeutic experience. Radical orchiectomy, as the standard treatment for YSTs, should be considered with caution in patients with bilateral testicular tumors. Rapid intraoperative frozen pathology provides support for timely surgical planning. In patients with intraoperative frozen pathologic specimens suggestive of benign lesions, testis-sparing surgery is the preferred treatment option.